Neither of those expressions is a binomial. [ 2y + 2xy ] is a binomial.
Monomial.
(x + y)2 = x2 + 2xy + y2
√18xy = √(9*2xy) = √9*√2xy = 3*√(2xy)
4xy - 2xy
Neither of those expressions is a binomial. [ 2y + 2xy ] is a binomial.
Monomial.
(x + y)2 = x2 + 2xy + y2
The binomial expression (x+y)^2 can be expanded using the formula x^2 + 2xy + y^2.
Since 2xy is a factor of 2x2y, it is automatically the GCF.
In mathematics, the expression 2xy represents the product of the number 2 and the variables x and y. This expression is known as a monomial, specifically a binomial because it consists of two terms. When simplified, 2xy cannot be further reduced unless additional information about the variables x and y is provided.
2xy + 6xy = 8xy
(x + 4y)(x - 6y)
√18xy = √(9*2xy) = √9*√2xy = 3*√(2xy)
The greatest common factor of 4xy and -6xy is 2xy. To find the greatest common factor, we first factor out the numbers 4 and -6 to get 2(2xy) and -2(3xy). The greatest common factor is the highest common factor that divides both terms evenly, which in this case is 2xy.
The three terms are: -3xy2, 2xy and -4y3
4xy - 2xy